2004
DOI: 10.1063/1.1763842
|View full text |Cite
|
Sign up to set email alerts
|

Binary phase behavior and aggregation of dilute methanol in supercritical carbon dioxide: A Monte Carlo simulation study

Abstract: Configurational-bias Monte Carlo simulations in the Gibbs and isobaric-isothermal ensembles using the transferable potentials for phase equilibria force field were carried out to investigate the thermophysical properties of mixtures containing supercritical carbon dioxide and methanol. The binary vapor-liquid coexistence curves were calculated at 333.15 and 353.15 K and are in excellent agreement with experimental measurements. The self-association of methanol in supercritical carbon dioxide was investigated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 25 publications
5
76
1
Order By: Relevance
“…closely resemble the conditions [37] for the presence of a hydrogen bonded complex. Thus, the local ordering of CO 2 molecules around heavy water indicates the possibility of existence of both EDA and hydrogen bonded moieties.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…closely resemble the conditions [37] for the presence of a hydrogen bonded complex. Thus, the local ordering of CO 2 molecules around heavy water indicates the possibility of existence of both EDA and hydrogen bonded moieties.…”
Section: Resultsmentioning
confidence: 63%
“…In order to identify the peak at 4.0 Å, we employ the standard geometric criteria [37] to define the hydrogen bond between D 2 O and CO 2 . These include conditions on the distance between the oxygen atoms, between D W and O C , as well as on the hydrogen bond angle.…”
Section: Resultsmentioning
confidence: 99%
“…To study the solution structure, Cabaco et al studied CO 2 + ethanol and acetone mixtures using Raman spectroscopy [15] and Stubbs and Siepmann studied CO 2 + methanol mixtures using Monte Carlo simulations [16]. The mobility was studied by Funazukuri et al, who reported binary diffusion coefficients in CO 2 + ketone mixtures [17].…”
Section: Introductionmentioning
confidence: 98%
“…These exhibit the typical behavior for strongly hydrogen bonding system with preferential aggregation. [51][52][53] The oxygen-hydrogen and oxygen-oxygen RDFs have pronounced and sharp peaks at the hydrogen bonding distances of 1.8 and 2.8Å, respectively. The RDFs also shown strong second peaks.…”
Section: Structural Analysis For the Binary Mixture Of Ethanol And Hfmentioning
confidence: 99%